Propuesta de productividad bajo un enfoque de sostenibilidad a partir de la economía circular. Estudio de caso: Natur Heilen SAS (2022)
Sustainability is currently an organizational tool that provides multiple benefits, including durability over time and a competitive advantage over other organizations, optimization of resources that leads to higher productivity and lower costs. The Natur Heilen SAS organization does not have any sustainable strategy in its production process, therefore, it is necessary to generate greater well-being inside and outside the organization. Creating, directing strategies and resources towards issues that are of vital importance worldwide, such as caring for the environment, compliance with the proposed sustainable objectives and hand in hand with this advance in productivity. In the organization there was no measurement of productivity, of its waste and there were no indicators to be precise about its procedures, in addition to the identification of delays and shortcomings that occur in the process and could be transformed into opportunities for improvement. constant.